Pengaruh Pelatihan Berpikir Positif terhadap Peningkatan Efikasi Diri Akademik pada Siswa SMA PGRI 3 Kota Padang - Yessy Septia Putri; Devi Rusli (Jurnal Halaqah, 2023)
This study aims to determine the effect of positive thinking training on increasing academic self-efficacy. This type of research is a quantitative quasi experiment with the nonrandomized pretest posttest group design.. The research subjects were 30 students of SMA PGRI 3 Padang City. The results showed that from the hypothetical framework it was found that there was an increase in the average score of the experimental group compared to the control group. This is evidenced by the different test Independent sample T-test with sig. (2-tailed) is worth 0.000. So that Ha is accepted, it can be concluded that positive thinking training has an effect on increasing the academic self-efficacy of SMA PGRI 3 Padang city students.